A PHARMACOGNOSTIC AND PHARMACOLOGICAL REVIEW ON CHROMOLAENA ODORATA (SIAM WEED) - Kanase, Vanita; Shaikh, Sana (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Chromolaena odorata is commonly known as Siam weed which belongs to sunflower family Asteraceae. C. odorata is an important medicinal plant which can be easily found in tropical Asia, West Africa, and parts of Australia. It is native to the America, and found in Florida and Texas in the United States, throughout Mexico and the Caribbean to South America. The medicinal usage of C. odorata has been reported in the traditional systems of medicine such as Ayurveda, Siddha, and Unani. It has wide variety of ethanomedicinal and pharmacological properties. The young leaves are crushed, and the resulting liquid can be used to treat skin wounds. The leaves extract is used by the kani tribals of Kouthalai in Tirunelveli hills to cure skin diseases, poison bites, wounds, and rheumatism. Following various folk claims for the ailment of various diseases, efforts have been made by the researchers to verify the efficacy of this weed through scientific biological screenings. A study of the literature revealed some notable pharmacological activities of the shrub such as anthelmintic, antimalarial, analgesic, anti-inflammatory, antipyretic, antispasmodic, antioxidant, antigonorrheal, antimycobacterial, insecticidal, fungicidal, wound healing, diuretic, blood coagulation, and antibacterial. The current review is created with an intent to focus on the numerous ethnobotanical and traditional uses as well as the phytochemical and pharmacological reports on C. odorata.